2015
DOI: 10.1558/jmea.v28i1.27499
|View full text |Cite
|
Sign up to set email alerts
|

Herding Strategies, Dairy Economy and Seasonal Sites in the Southern Alps

Abstract: This paper investigates one of the main issues of the archaeology of pastoralism in the southern Alps: the decrease of upland archaeological evidence in the late Iron Age (IA) and the Roman period. A novel interpretation is proposed using ethnoarchaeological, ethnographic and ethnohistoric data collected in different areas of the French and Italian Alps. These data document the existence of two pastoral strategies: Alpine pastoralism (focused on dairying activity) and transhumance (mainly focused on the exploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Interestingly, the ceramics containing dairy fats are associated with stone structures ( Fig 1C ) suggesting that the latter were an essential part of dairy focused alpine pastoralism. Similar structures are used by modern alpine pastoralists for the production of cheese during the summer months [ 34 , 35 ]. As these structures are found several hundred years earlier in other parts of the Alps [ 16 ], an earlier origin for alpine dairying may be postulated but harder to demonstrate given the lack of artefacts at these sites.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the ceramics containing dairy fats are associated with stone structures ( Fig 1C ) suggesting that the latter were an essential part of dairy focused alpine pastoralism. Similar structures are used by modern alpine pastoralists for the production of cheese during the summer months [ 34 , 35 ]. As these structures are found several hundred years earlier in other parts of the Alps [ 16 ], an earlier origin for alpine dairying may be postulated but harder to demonstrate given the lack of artefacts at these sites.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the world, investigations of mobile pastoralism have by now generated a significant corpus of archaeological data (Honeychurch and Makarewicz 2016). Ethnoarchaeological work (Biagetti 2014;Carrer 2015;Wright 2016) continues to aid in the interpretation of the often substantial and archaeologically recognizable remains left behind, particularly at habitation sites. Advances in biomolecular research are revolutionizing our ability to understand pastoralist subsistence systems (Dunne et al 2012) and herd management practices (Janzen 2015).…”
Section: Introductionmentioning
confidence: 99%
“…What we have not found is evidence of intensified pastoralism, in the form of shielings, byres, pens, or similar installations. The signature of specialized transhumant pastoralism in European mountains is well known both ethnographically and archaeologically (Bartosiewicz and Greenfield 1999;Berruti et al 2016;Carrer 2013Carrer , 2015Carrer and Angelucci 2018;Christie et al 2007;Mientjes 2004;Moe and Fedele 2019;Putzer et al 2016;Stagno 2017;Visentin et al 2016;Walsh et al 2014). Such studies in the Alps, Pyrenees, and elsewhere have revealed the extensive infrastructure needed to support specialized pastoralism.…”
Section: Early Modern Through Nineteenth Centurymentioning
confidence: 98%